(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Background There is an increasing occurrence of children with G6PD deficiency that affects the experiences of their primary caregiver. Objective This study focused on the experiences of parents of children with G6PD deficiency with the disease, experiences of parents in the management at home and in the community, and with the Health Care System. Methodology The study utilized qualitative research specifically, Husserlian phenomenology. The seven participants were chosen through criterion sampling with the approval of the Ethics Review Board prior to the gathering of data. The data were collected from January 2022 – February 2022. Giorgi’s method of interpretation was utilized in analyzing data and was simultaneously done with data gathering. Findings The themes that emerged from the study were the umbra, penumbra, and antumbra. The participants expressed that their experiences are likened to a silhouette. It represents the experiences of the participants when they narrated that they feel like they were in the darkest moment of their lives upon knowing the diagnosis of their child until such time that they finally accepted the reality and must live with it, like the shadow that doesn’t fade, that vague feeling will always be there. Recommendations Therefore, healthcare providers need to create a delicate balance between being informative, sympathetic, and supportive to the mothers regarding G6PD deficiency. The government should provide a Newborn Screening education on mothers focused on needed information. And the education should be provided mainly by healthcare providers and supplemented by educational material. Lastly, more studies should be conducted in areas that were not explored in this study.